Spectrum And Antimicrobial Susceptibility Pattern Of Isolates In Neonatal Sepsis - Kumar, Vivek; Saini, Narendra; Kumar, Gunjana (Journal of Neonatal Surgery, 2025)
Introduction: Neonatal sepsis is a significant cause of morbidity and mortality, particularly in developing countries. Identifying causative pathogens and their antimicrobial resistance patterns is critical for effective management. This study aimed to assess microbial diversity, antimicrobial resistance, and recommend effective treatment strategies for neonatal sepsis at a tertiary care hospital. Material & Methods: This study was carried out at the Department of Microbiology, National Institute of Medical Sciences and Research. A total of 120 neonates with suspected sepsis were included. Blood cultures were performed using the BacT/ALERT system, and antimicrobial susceptibility testing followed CLSI guidelines. Results: Of 120 neonates, 59 (49.2%) had EOS and 61 (50.8%) had LOS. Blood culture positivity was 44/120 (36.7%). The most common isolates were Klebsiella pneumoniae (31.8%), Pseudomonas aeruginosa (11.4%), and Staphylococcus aureus (4.5%). Gram-negative isolates showed 100% resistance to ceftriaxone and cefotaxime, 82.1% to imipenem, and 75.0% to meropenem. Colistin (100% sensitivity, p < 0.001) and tigecycline (95.7%, p = 0.002) were the most effective agents. Conclusion: The study highlights a high prevalence of Gram-negative bacterial infections and rising antimicrobial resistance in neonatal sepsis. Based on resistance patterns, colistin, tigecycline, and minocycline should be considered for multidrug-resistant infections, while glycopeptides (vancomycin, teicoplanin) remain effective for Gram-positive infections. The findings emphasize the need for routine surveillance, antimicrobial stewardship, and judicious antibiotic use to optimize neonatal sepsis treatment